Strategic applications of named reactions in organic synthesis : - Kulrti, László (Elsevier Academic Press, 2005)
"...no other book covers the subject of named reactions in such an up-to-date and comprehensive way, ranging from mechanisms to applications. Despite it's minor weaknesses, I recommend this book most emphatically to interested chemists as a work of reference and source of inspiration."